Antinociceptive evaluation of an ethanol extract of Achyranthes aspera (agadha) in animal models of Nociception. - Bhosale Uma,; Radha Yegnanarayan,; Pophale Prachi,; Mandar Zambare,; R.S. Somani, (International Journal of Phytomedicine, 2010)
Achyranthes aspera Linn., known as Chirchira (Hindi), Agadha (Marathi) is an indigenous herb found in India. It is the basic composition of many traditional remedies. The herb has been reported to have variety of activities like antifertility, antihyperlipidemic, antidiabetic, immunomodulatory, anticarcinogenic, diuretic and cardiotonic, anti-inflammatory, antifungal and antibacterial activity. Present study was designed to evaluate the antinociceptive activity of ethanolic extract of A. Aspera (EEAA) and to find the phytochemical responsible for this activity with possible mode of its activity. The antinociceptive activity of ethanol extract of Achyranthes aspera was investigated in albino mice. The pharmacological assays used were the tail flick, hot plate and the formalin-induced pain tests. The extract was given intraperitoneally at a dose of 400 mg/kg (our earlier study revealed no activity at the dose 200mg/kg). Pentazocine (10mg/kg body weight i.p.) was used as standard. Data analyzed by ANOVA test followed by Dunnett’s test. All the results were expressed as Mean (±SEM). P <0.05 was considered significant. For formalin test the percent inhibition was calculated by using formula (C-T)/C × 100 (%). Phytochemical screening revealed presence of triterpenoid saponins possessing oleanolic acid as aglycone, viz. A & B, alkaloid achyranthine, water soluble base betaine and steroids. In the tail flick & hot plate test extract treated animals showed significant analgesic activity at 30, 60, 90 and 120min. Extract (400 mg/kg i.p.) reduced the formalin induced pain in both phases (i.e. neurogenic and inflammatory) by 58.8% and 92.7%, respectively. Ethanol extract of A.Aspera exhibit central as well as peripheral antinociceptive activity.